The effect of implementation and data quality on continuance intention in using the Sistem Informasi Penilaian (SIP DJKN), mediated by service quality - Sairin Sairin; Yudha Budi Abadi; Siti Nur Azizah (Institute of Computer Science (IOCS), 2026)
The implementation of Sistem Informasi Penilaian (SIP - DJKN) has intensified the need for public organizations to strengthen employee performance through digital adaptation and effective leadership practices for increase public services. The research adopts a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were collected from 103 respondents, consisting of employees within the Directorate General of State Assets (DJKN) and related stakeholders through Purposive sampling using structured questionnaires with Likertscale measurements. The findings indicate that both system implementation and data quality positively and significantly influence continuance intention. Furthermore, service quality plays a critical mediating role in strengthening these relationships. The results highlight the importance of improving service responsiveness and ensuring high-quality data to sustain long-term system adoption in public sector digital transformation. This study contributes to the literature by confirming the importance of service quality as a mediator in public sector digital systems